(Hi-)Stories of the Gulag: fiction and reality - Fischer von Weikersthal, Felicitas; Thaidigsmann, Karoline (Universitätsverlag Winter, 2016)
Cover -- Title Page -- Copyright -- Contents -- Introduction. Felicitas Fischer von Weikersthal, Karoline Thaidigsmann -- Galina IVANOVA, Competing Realities: Statistics, Memoirs and the History of the Gulag [Die Gulag-Statistiken im Spiegel von Archivmaterialien und Memoiren] -- Dan HEALEY, "Dramatological" Trauma in the Gulag. Malingering, Self-Inflicted Injuries and the Prisoner-Patient -- Friedrich GEIGER, Music in the Recollections of Political Gulag Prisoners -- Felicitas Fischer VON WEIKERSTHAL, Appearance and Reality. Nazi Germany and Gulag-Memoirs -- Manuela PUTZ, „Auf dem Weg nach vorne. Polithäftlinge sind wir". Politische Gefangenschaft, transnationale Netzwerke und Identitätskonstruktionen Andersdenkender in der Sowjetunion der 1960er bis 1980er Jahre -- Zuzanna BOGUMIŁ, The Solovetski Islands and Butovo as two "Russian Golgothas". New Martyrdom as a Means to Understand Soviet Repression -- Anne HARTMANN, Fiction and Reality: Literary Testimonies Between Document and Fictionalization Erschöpft und usurpiert. Plädoyer für ein erweitertes Konzept von Gulag-Literatur -- Andrea GULLOTTA, Gulag Poetry. An Almost Unexplored Field of Research -- Leona TOKER, Rereading Varlam Shalamov's Stories June and May. Four Kinds of Knowledge -- Alfred GALL, Disconcerting Concision. Laconism as Principle of Text Organization - Leo Lipski (Dzień i noc) and Lev Konson (Kratkie povesti) -- Łukasz Neca, Fiktive Wirklichkeiten - wirkliche Fiktionen. Gustaw Herling-Grudzinskis Inny swiat und Wlodzimierz Odojewskis Zabezpieczanie sladów -- Renate LACHMANN, Document or Fiction? Karlo Štajner and Danilo Kiš -- Karoline THAIDIGSMANN, Inventing the Gulag: Approaches in Contemporary Literature, Music and Film Visitors to the Gulag. Soviet Forced Labor in Contemporary Western Fiction for Adult and Young Readers.
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2012 -- Heidelberg; Geschichte 1923-1937; Presse; Arbeitslager; Sowjetunion; Straflager; Autobiografische Literatur; Slawische Sprachen; Literatur